2019
DOI: 10.1111/aej.12374
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to cyclic fatigue of reciprocating instruments determined at body temperature and phase transformation analysis

Abstract: The purpose of this study was to compare cyclic fatigue (CF) resistance of reciprocating instruments at body temperature and relate the findings to their martensitic transformation temperatures. Contemporary nickel-titanium (NiTi) reciprocating instruments WaveOne Primary, WaveOne Gold Primary and EdgeFile X1 (n = 20 each and #25 tip diameter) were tested for CF resistance at body temperature (37 AE 1°C). Instruments were actioned according to manufacturer guidelines until fracture occurred in a simulated cana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 40 publications
(54 reference statements)
2
18
0
1
Order By: Relevance
“…Recent studies have convincingly demonstrated a higher CF resistance of instruments with new alloys and designs; however, low-cost instruments are being incorporated to the market and a lower reliability has been reported to be expected when using such offerings (12,22). We suggest that minimum criterion be implemented for manufacturers to demonstrate the reliable use of new instruments in clinical settings, before marketing a new product.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Recent studies have convincingly demonstrated a higher CF resistance of instruments with new alloys and designs; however, low-cost instruments are being incorporated to the market and a lower reliability has been reported to be expected when using such offerings (12,22). We suggest that minimum criterion be implemented for manufacturers to demonstrate the reliable use of new instruments in clinical settings, before marketing a new product.…”
Section: Discussionmentioning
confidence: 92%
“…At the same time, new martensitic alloys have demonstrated superior fatigue behavior (6,12). Most CF studies of NiTi files have been performed at room temperature, however recent literature confirmed that sodium hypochlorite placed in root canals at room temperature rapidly approached body temperature (13).…”
Section: Introductionmentioning
confidence: 99%
“…13,[24][25] A study evaluating CFR of reciprocating instruments made of Fire-Wire, Gold wire and M wire showed that instrument made of Fire-Wire exhibited higher CFR at body temperature than made of Gold wire and M-Wire. 23 Gündoğar et al evaluated that the CFR of 4 different NiTi rotary files in their study and ROTATE showed higher CFR than all the tested files. 26 A study comparing of the CFR of ROTATE with both reciprocating and continuous rotary NiTi instruments showed that ROTATE showed higher CFR than the Mtwo and Reciproc files, but lower CFR than Reciproc Blue file.…”
Section: Discussionmentioning
confidence: 98%
“…The development of heat-treated files has achieved a significant breakthrough in modern endodontics and at the same time, provided reduced risk of fractured of endodontic files during the instrumentation of curved and narrow canals. 23 The current study evaluated the CFR of new instruments that work with a rotary motion (ROTATE, K3XF, and ETP). Based on the findings of the study, the null hypothesis was rejected because there was a significant difference in CFR among the files in an Sshaped canal.…”
Section: Discussionmentioning
confidence: 99%
“…This also ensures that compression and tensile stress cycles are localized at the maximum flexure point [22], distributes the shear resistance homogeneously along the NiTi endodontic rotary instrument surface, and leads to the formation of microcracks on the instruments' microstructure [23] without any signs of plastic deformation in the static model; the area of these stresses spreads through the instrument shaft in the dynamic model [21]. Most of the static and dynamic custom-made cyclic fatigue devices provided a non-instrument-based artificial root canal [24,25], so the results extracted from these studies should be carefully considered and not applied to clinical practice. Di Nardo et al reported statistically significant differences (p < 0.05) between the time to failure of Wave One Gold NiTi endodontic reciprocating files (50.75 ± 20.06 s) and Reziflow (30.13 ± 9.40) conventional NiTi endodontic rotary instruments [26].…”
Section: Discussionmentioning
confidence: 99%